WEISSENBERG DATA-COLLECTION FOR MACROMOLECULAR CRYSTALLOGRAPHY - Stuart, D; Jones, E (1993)
The Weissenberg method has recently emerged as a viable technique in protein crystallography with the demonstration of fast, efficient X-ray diffraction data collection from a variety of protein crystals by this method at the Photon Factory (Tskuba, Japan). This review assesses the technique in the context of current results and future developments.